2015
DOI: 10.1002/prp2.159
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of SMM‐189, a cannabinoid receptor 2‐specific inverse agonist

Abstract: Cannabinoid receptor 2 agonists and inverse agonists are emerging as new therapeutic options for a spectrum of autoimmune-related disease. Of particular interest, is the ability of CB2 ligands to regulate microglia function in neurodegenerative diseases and traumatic brain injury. We have previously reported the receptor affinity of 3′,5′-dichloro-2,6-dihydroxy-biphenyl-4-yl)-phenyl-methanone (SMM-189) and the characterization of the beneficial effects of SMM-189 in the mouse model of mild traumatic brain inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 71 publications
3
48
0
Order By: Relevance
“…We have previously reported this method as part of our pre-clinical evaluation of SMM-189. 44 The method provided good correlation between the K i and EC 50 values; however, the K i deviated significantly from the previous determination 48 in part due to differences in K d and B max of the preparations. A second consideration stemmed from the identification that SMM-189 is a non-competitive antagonist against CP 55,940, thus indicating an overlapping binding site.…”
Section: Receptor Binding and Functional Assaysmentioning
confidence: 93%
See 4 more Smart Citations
“…We have previously reported this method as part of our pre-clinical evaluation of SMM-189. 44 The method provided good correlation between the K i and EC 50 values; however, the K i deviated significantly from the previous determination 48 in part due to differences in K d and B max of the preparations. A second consideration stemmed from the identification that SMM-189 is a non-competitive antagonist against CP 55,940, thus indicating an overlapping binding site.…”
Section: Receptor Binding and Functional Assaysmentioning
confidence: 93%
“…48 In the evaluation of the functional activity of the compounds it was discovered that SMM-189 exhibited selective inverse agonist activity at CB2. 44 Based on the potential of CB2 inverse agonist in treating CNS diseases, we demonstrated that SMM-189 beneficially down-regulates cytokine and chemokine production in LPS stimulated primary human microglia. 25,44 Subsequent testing of SMM-189 in the murine model of mild traumatic brain injury (mTBI), and pre-clinical evaluation of biopharmaceutical properties, demonstrated the protective effects of SMM-189 in mTBI and indicated that the 2,6-dihydroxy-biphenyl-aryl-methanone scaffold has acceptable drug-like properties to warrant further investigation.…”
Section: Figure 1 Structures Of Selected Cb2 Inverse Agonistsmentioning
confidence: 98%
See 3 more Smart Citations